Management Measures and Trends of Biological Invasions in Europe: A Survey‐Based Assessment of Local Managers - Carla Garcia‐Lozano; Josep Pueyo‐Ros; Quim Canelles; Guillaume Latombe; Tim Adriaens; Sven Bacher; Ana Cristina Cardoso; Michelle Cleary; Lluís Coromina; Franck Courchamp; Wayne Dawson; Maarten de Groot; et al. (Global Change Biology, 2025)
Biological invasions are a major threat to biodiversity, ecosystem functioning and nature's contributions to people worldwide. However, the effectiveness of invasive alien species (IAS) management measures and the progress toward achieving biodiversity targets remain uncertain due to limited and nonuniform data availability. Management success is usually assessed at a local level and documented in technical reports, often written in languages other than English, which makes such data notoriously difficult to collect at large geographic scales. Here we present the first European assessment of how managers perceive trends in IAS and the effectiveness of management measures to mitigate biological invasions. We developed a structured questionnaire translated into 18 languages and disseminated it to local and regional managers of IAS in Europe. We received responses from 1928 participants from 41 European countries, including 24 European Union (EU) Member States. Our results reveal substantial efforts in IAS monitoring and control, with invasive plants being the primary focus. Yet, there is a general perception of an increase in the numbers, occupied areas, and impacts of IAS across environment and taxonomic groups, particularly plants, over time. This perceived increase is consistent across both EU and non‐EU countries, with respondents from EU countries demonstrating more certainty in their responses. Our results also indicate a lack of data on alien vertebrates and invertebrates, reflecting a need for more targeted monitoring and knowledge sharing between managers and policymakers and between countries. Overall, our study suggests that Europe's current strategies are insufficient to substantially reduce IAS by 2030 and hence to meet the Kunming‐Montreal Global Biodiversity Framework target.

Green financing and sustainability reporting among SMEs: The role of pro-environmental behavior and digitization - Elias Appiah-Kubi; Francisca Omama Koranteng; Codruța Cornelia Dura; Alin Adrian Mihăilă; Imola Drigă; Ana Preda (Journal of Cleaner Production, 2024)

Using the IUCN Environmental Impact Classification for Alien Taxa to inform decision‐making - Sabrina Kumschick; Sandro Bertolino; Tim M. Blackburn; Giuseppe Brundu; Katie E. Costello; Maarten de Groot; Thomas Evans; Belinda Gallardo; Piero Genovesi; Tanushri Govender; Jonathan M. Jeschke; Katharina Lapin; et al. (Conservation Biology, 2024)
The Environmental Impact Classification for Alien Taxa (EICAT) is an important tool for biological invasion policy and management and has been adopted as an International Union for Conservation of Nature (IUCN) standard to measure the severity of environmental impacts caused by organisms living outside their native ranges. EICAT has already been incorporated into some national and local decision‐making procedures, making it a particularly relevant resource for addressing the impact of non‐native species. Recently, some of the underlying conceptual principles of EICAT, particularly those related to the use of the precautionary approach, have been challenged. Although still relatively new, guidelines for the application and interpretation of EICAT will be periodically revisited by the IUCN community, based on scientific evidence, to improve the process. Some of the criticisms recently raised are based on subjectively selected assumptions that cannot be generalized and may harm global efforts to manage biological invasions. EICAT adopts a precautionary principle by considering a species’ impact history elsewhere because some taxa have traits that can make them inherently more harmful. Furthermore, non‐native species are often important drivers of biodiversity loss even in the presence of other pressures. Ignoring the precautionary principle when tackling the impacts of non‐native species has led to devastating consequences for human well‐being, biodiversity, and ecosystems, as well as poor management outcomes, and thus to significant economic costs. EICAT is a relevant tool because it supports prioritization and management of non‐native species and meeting and monitoring progress toward the Kunming–Montreal Global Biodiversity Framework (GBF) Target 6.

Developing a list of invasive alien species likely to threaten biodiversity and ecosystems in the European Union - Helen E. Roy; Sven Bacher; Franz Essl; Tim Adriaens; David C. Aldridge; John D. D. Bishop; Tim M. Blackburn; Etienne Branquart; Juliet Brodie; Carles Carboneras; Elizabeth J. Cottier-Cook; Gordon H. Copp; et al. (Global Change Biology, 2019)
The European Union ( EU ) has recently published its first list of invasive alien species ( IAS ) of EU concern to which current legislation must apply. The list comprises species known to pose great threats to biodiversity and needs to be maintained and updated. Horizon scanning is seen as critical to identify the most threatening potential IAS that do not yet occur in Europe to be subsequently risk assessed for future listing. Accordingly, we present a systematic consensus horizon scanning procedure to derive a ranked list of potential IAS likely to arrive, establish, spread and have an impact on biodiversity in the region over the next decade. The approach is unique in the continental scale examined, the breadth of taxonomic groups and environments considered, and the methods and data sources used. International experts were brought together to address five broad thematic groups of potential IAS . For each thematic group the experts first independently assembled lists of potential IAS not yet established in the EU but potentially threatening biodiversity if introduced. Experts were asked to score the species within their thematic group for their separate likelihoods of i) arrival, ii) establishment, iii) spread, and iv) magnitude of the potential negative impact on biodiversity within the EU . Experts then convened for a 2‐day workshop applying consensus methods to compile a ranked list of potential IAS . From an initial working list of 329 species, a list of 66 species not yet established in the EU that were considered to be very high (8 species), high (40 species) or medium (18 species) risk species was derived. Here, we present these species highlighting the potential negative impacts and the most likely biogeographic regions to be affected by these potential IAS.